2021
DOI: 10.1101/2021.06.30.450566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short homology-directed repair using optimized Cas9 in the pathogen Cryptococcus neoformans enables rapid gene deletion and tagging

Abstract: Cryptococcus neoformans, the most common cause of fungal meningitis, is a basidiomycete haploid budding yeast with a complete sexual cycle. Genome modification by homologous recombination is feasible using biolistic transformation and long homology arms, but the method is arduous and unreliable. Recently, multiple groups have reported the use of CRISPR-Cas9 as an alternative to biolistics, but long homology arms are still necessary, limiting the utility of this method. Since the S. pyogenes Cas9 derivatives us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…For targeted gene disruption and deletion, previous studies have reported that flanking homologies ranging in length from 30 to 2000 bp can yield efficient homology-directed repair after DNA double-strand breaks induced by Cas9 in aspergilli, Rhizopus microspores and C. neoformans (Huang et al, 2022;Lax et al, 2021;Nodvig et al, 2018). Therefore, based on the protocols used for gene deletion in Magnaporthe oryzae and Aspergillus species (Foster et al, 2018;Peres da Silva and Brock, 2022), we developed a CRISPR/Cas9-based protocol for gene disruption in S. brasiliensis and S. schenckii.…”
Section: Discussionmentioning
confidence: 99%
“…For targeted gene disruption and deletion, previous studies have reported that flanking homologies ranging in length from 30 to 2000 bp can yield efficient homology-directed repair after DNA double-strand breaks induced by Cas9 in aspergilli, Rhizopus microspores and C. neoformans (Huang et al, 2022;Lax et al, 2021;Nodvig et al, 2018). Therefore, based on the protocols used for gene deletion in Magnaporthe oryzae and Aspergillus species (Foster et al, 2018;Peres da Silva and Brock, 2022), we developed a CRISPR/Cas9-based protocol for gene disruption in S. brasiliensis and S. schenckii.…”
Section: Discussionmentioning
confidence: 99%
“…Primers used in this work are listed in Supplemental File 2. All genetic manipulations were done using CRISPR-mediated gene editing and the TRACE system following previously published protocols 51,52 . Briefly, gRNAs were generated using guide-specific primers and amplification from the pBHM2329 plasmid (gift from H. Madhani).…”
Section: Strain Construction and Molecular Biologymentioning
confidence: 99%
“…The application of similar CRISPRa systems to other fungal organisms would lend further insight into fungal biology across this kingdom. Many CRISPR tools have been developed in a diversity of fungal organisms (Muñoz et al 2019;Cai et (Fan and Lin 2018;Wang 2018;Huang et al 2021) and Aspergillus fumigatus (Fuller et al 2015;Zhang et al 2016;Al Abdallah et al 2018;van Rhijn et al 2020).…”
Section: ) Non-crispr Overexpression Libraries That Have Previously B...mentioning
confidence: 99%
“…The application of similar CRISPRa systems to other fungal organisms would lend further insight into fungal biology across this kingdom. Many CRISPR tools have been developed in a diversity of fungal organisms (17,22,(135)(136)(137)(138)(139), including numerous nonalbicans Candida species (11,(140)(141)(142)(143)(144)(145)(146), and other prominent pathogens such as Cryptococcus neoformans (147)(148)(149) and Aspergillus fumigatus (150)(151)(152)(153). These CRISPR platforms could be adapted to similar CRISPRa tools in these organisms, with many possible applications for the analysis of pathogen biology or drug target identification (49)(50)(51)(52)154).…”
Section: Harnessing the Cell's Natural Transcriptional Machinery To I...mentioning
confidence: 99%